Numerical analysis of the tunnel-soil interaction caused by an explosion in the tunnel. Issue 122 (July 2019) - Osinov, Vladimir A.; Chrisopoulos, Stylianos; Triantafyllidis, Theodoros
Abstract: The paper presents a numerical analysis of the dynamic deformation of the tunnel lining and the soil caused by a blast-induced pressure pulse of a moderate amplitude (several megapascals) inside the tunnel. The tunnel lining is circular and consists of individual concrete linearly elastic tubbings. The tunnel is located at a depth of 15 m in fully saturated granular soil. Effective-stress changes are described by a hypoplasticity model. The possibility of pore water cavitation at zero absolute pore pressure is taken into account. The problem is solved in a two-dimensional plane-strain formulation with the finite-element program Abaqus/Standard. Emphasis is placed on fine spatial discretization in order to obtain accurate solutions. Stresses and deformations in the lining and in the soil are analysed in detail. The solutions reveal an important role of the strong nonlinearity in the soil behaviour due to the pore water cavitation. Abstract : Highlights: An explosion in a tunnel surrounded by fully saturated soil is modelled. An explosion produces tensile as well as compressive deformations of the soil. Pore water cavitation and the ground surface play an important role in the process.